Women Safety Technique Using IoT Devices (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Today in the current overall circumstance, the eminent request in every youngster's mind, considering the reliably rising addition of issues on women incitement in the new past is generally about her prosperity and security. The potentially thought frequenting every young woman is where they will really need to move uninhibitedly on the streets even in odd hours without worrying about their security. This paper prescribes another perspective to use advancement for women's security. "848 Indian Women Are Harassed, Raped, Killed Every Day!!" That's a far past HUGE number! We propose an idea that changes the way wherein everyone considers women's prosperity. A day when media conveys a more noteworthy measure of women's achievements rather than incitement, it's an achievement achieved! Since we (individuals) can't respond reasonably in essential conditions, the necessity for a device that normally resources and rescues the setback is the undertaking of our idea in this paper. We propose to have a device that is the blend of different contraptions; hardware incorporates a wearable "Splendid band" which continually talks with Smartphone that methodologies the web. The application is altered and stacked with all the vital data which joins Human direct and reactions to different conditions like dismay, fear, and anxiety. This delivers a sign which is shipped off the mobile phone. The item or application approaches GPS and Messaging organizations which are pre-changed so that whenever it gets the emergency signal, it can send help interest close by the space headings to the nearest Police station, relatives, and people near range who have application. This action engages help rapidly from the Police similarly as the Public in the near range that can show up at the loss with unprecedented exactness. This article moves around the privacy in terms of providing very guaranteed in terms of privacy for women so by that it feels more powerless at the time of friendly situations. To improve more we are designing the model with the help of high level microcontroller and named as STM32F407VG Micro-Controller.